As expressões dos impactos do mundo do trabalho no estágio supervisionado em Serviço Social - Curtis, Kelvin Henrique Bernardo (2018)
The referred dissertation leads the discussion about the impacts of the world of work on supervised Service Social Work. In this sense, it will be approached the conjuncture of higher education, the structuring of the world of work, and the singularities of the supervised stage as a discipline that makes up the higher education in Social Service. In this way, it is based on the multi-case study of two higher education institutions in the interior of Rio Grande do Sul, one of public, faceto-face and one of private nature of distance learning, that give empirical subsidies to address the particular elements that interpose the relation of the stage and the supervision in these spaces of formation. It was therefore necessary to unveil the relationship and mediation of the world of work with the supervised internship in Social Service.